BUSINESS AND ITS CHALLENGES IN GEORGIA - Maia Aladashvili; Nanuli Khizanishvili (Scholar Express Journals, 2022)
Insurance - is one of the financial tools of risk management, which allows to avoid financial losses caused by risk. Insurance has a great role and importance in the development of the public reproductive process. The importance of insurance is expressed in the so-called of insurance services that facilitate the expansion of the reproductive process of economic entities. Insurance, as a subset of financial relations, has a special role in the development of business and as an economic category, it is a system of economic relations, which enables the formation of funds and their use compensates losses in the event of various adverse cases. This paper presents the problems facing the insurance business in Georgia and their solutions
Keywords: Insurance; Business; Risks; Financial Losses And Challenges